Comparative analysis of humoral immune responses and pathologies of BALB/c and C57BL/6 wildtype mice experimentally infected with a highly virulent Rodentibacter pneumotropicus (Pasteurella pneumotropica) strain - Juliane Fornefett (BMC Microbiology, 2018)
Abstract Background Mice are a natural host for Rodentibacter (R.) pneumotropicus. Despite specific monitoring, it is still one of the most important infectious agents in laboratory animals. The objective of this study was to determine the virulence of a prevalent pathotype of R. pneumotropicus and characterize the host response in a new animal model. Results Intranasal infection of C57BL/6 and BALB/c mice with a R. pneumotropicus strain (JF4Ni) bearing the genes of the three known repeats in toxin (RTX) toxins resulted in an unprecedented high mortality and morbidity above 50 and 80%, respectively. Morbidity was associated with severe weight loss as well as conjunctivitis and dyspnea. A main pathology was a catarrhal purulent to necrotic bronchopneumonia. Specific immune globuline (Ig) A was detected in tracheonasal lavages of most surviving mice which were still colonized by R. pneumotropicus. Furthermore, all surviving animals showed a distinct production of IgG antibodies. To differentiate T-helper cell (Th) 1 and Th2 immune responses we used subclasses of IgGs as indicators. Mean ratios of IgG2b to IgG1 were below 0.8 in sera drawn from both mice strains prior infection and from BALB/c mice post infection. In contrast, C57BL/6 mice had a mean IgG2b/IgG1 ratio of 1.6 post infection indicating a Th1 immune response in C57BL/6 versus a Th2 response in BALB/c mice associated with a tenfold higher bacterial load in the lung. In accordance with a Th1 response high antigen-specific IgG2c titers were detected in the majority of surviving C57BL/6 mice. Conclusions R. pneumotropicus JF4Ni is a highly virulent strain causing severe pneumonia and septicemia after intranasal infection of C57BL/6 and BALB/c mice. Persisting infections in the two mice strains are associated with Th1 and Th2 immune responses, respectively, and differences in the bacterial burden of the lung. The described model is ideally suited for future vaccination studies using the natural host.